153k views
0 votes
When the sum of a certain number and 1 is multiplied by 3, the result is 6. Which equation below matches this description?

Question 1 options:

x+3=6

x+1/3 =6

3x=6

3x+1=6

3(x+1)=6

2 Answers

5 votes

Answer: 3(x+1)=6

Step-by-step explanation: I took the test got 100%

User Fcsr
by
5.0k points
1 vote

Answer:

Option E: 3(x+1)=6

Explanation:

The sum of a certain number plus 1 means x + 1. Then, the question states that the sum of those two numbers are multiplied by three: 3(x+1). Finally, the last part of the question is that the equation is equal to 6. Thus, 3(x+1)=6.

User Laurieann
by
5.2k points